Effect of Guided Imagery on Sleep Quality and General Health of the Elderly - Mahdieh Heidarian; Farahnaz Mohammadi Shahbalaghi; Shamaneh Mohammadi; Nasim Sadeghi Mahalli; Mehdi Noroozi; Nazila Vosoghi (University of Social Welfare & Rehabilitation Sciences, 2023)
Objectives Sleep disorders are among the most common problems in the elderly. Guided imagery is a non-pharmacological treatment that can be effective in treating these problems and improving the health of the elderly. This study aims to determine the effect of guided imagery therapy on sleep quality and general health of older adults suffering from sleep disorders. Methods & Materials This is an interventional study on 70 older adults aged >60 years referred to a health center in Ardabil, Iran in 2021. They were selected using a convenience sampling method and were randomly allocated to the intervention (n=35) and control (n=35) groups after obtaining informed consent. The Pittsburgh sleep quality index (PSQI) and Goldberg's general health questionnaire (GHQ) were used before and after the intervention for data collection. The control group received the routine care, while the intervention group received the guided imagery therapy as well by listening to an audio file. Data analysis was done in SPSS software, version 22. Results There was no significant difference in the mean score of PSQI and GHQ between the two groups before the intervention (P>0.05). However, a significant difference was observed in sleep quality (P≤0.001) and general health (except for severe depression and social dysfunction domains) after the intervention (P≤0.05). Conclusion Guided imagery is efficient in improving sleep quality and general health of the elderly with sleep disorders and can be used as a non-pharmacological nursing intervention.